2018
DOI: 10.1080/09297049.2018.1497588
|View full text |Cite
|
Sign up to set email alerts
|

Building capacity in neurodevelopment assessment of children in sub-Saharan Africa: A quality assurance model to implement standardized neurodevelopment testing

Abstract: Compromised neurodevelopment (ND) among infants and children is prevalent in sub-Saharan Africa. Standardized testing of ND is frequently prohibitive in these contexts, as tests require skilled staff for their application. In this paper, we present a quality assurance (QA) model (QualiND) for standardized ND testing, discussing findings and implications from our experience applying the Kaufman Assessment Battery for Children second edition (KABC-II). The QualiND model was implemented within IMPAACT P1104s stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…The tests outcomes were previously described in a validation study of the present neuropsychological measures [6]. The quality assurance process for administering the tests has also been previously described [10], as has adaptation of all tests in the local languages [1].…”
Section: Assessmentsmentioning
confidence: 99%
“…The tests outcomes were previously described in a validation study of the present neuropsychological measures [6]. The quality assurance process for administering the tests has also been previously described [10], as has adaptation of all tests in the local languages [1].…”
Section: Assessmentsmentioning
confidence: 99%
“…Deficits in neurocognition in children may significantly impact future learning, class performance and academic attainment [ 20 ]. However, in routine clinical practice in the African setting, assessment of neurodevelopment in children surviving illnesses like SA is not integrated in routine clinical care [ 21 , 22 ]. An earlier study that examined neurodevelopmental outcomes amongst Ugandan children < 5 years surviving severe malaria anaemia (SMA), a form of complicated malaria showed that SMA was associated with long-term cognitive impairment [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results are also consistent with those reported for other tests of early childhood development adapted and translated for Ethiopian (Hanlon et al, ) and Nepalese (Ranjitkar et al, ) children. Although other previous studies in low resource settings have documented adequate interrater reliability for tests developed for school‐age children (Ruiseñor‐Escudero et al, ), it is encouraging that high interrater reliability is also being achieved for early childhood assessments, as these assessments generally require a higher level of skill and training of test administrators and so are more vulnerable to errors in administration and scoring.…”
Section: Discussionmentioning
confidence: 86%